The Effect of Climate and Environment on Human Mental State and Health - Fayaz Gul Mazloum Yar; Mohammad Ishaq Shaheedzooy (Riviera Publishing, 2024)
Height is one of the structural factors that most influences the earth's environment. Access to varying temperatures has created many challenges for animal health. Addressing ecological problems through temperature reduction and subsequent recovery of animal growth has become one of the most important topics of modern times, accessible through ecology and fundamental change. Climatology covers many fields of study, not only within the branch of atmospheric science but also involving issues of animal ecology. This significant form of intelligence can control various human needs, such as food, energy, health, physical and mental well-being, and much more. This analysis was carried out through the library abstraction method. Based on the following titles and keywords, various sources, including acceptable anesthesia books and accessories about the anniversary of acute equipment such as air pressure, temperature, humidity, solar radiation, wind, and the influence of rainfall on brain and brain health and disease, studied. It appears that climate, which includes elements such as wind, rain, and snow, can play an influential role in animal emotions. Considering that these natural phenomena have different environments in our lives, considering them can contribute to improving the quality of the brain and brain in our daily life.